(3Jhajb GdYfGjI aj TQM GdhbGjIs - (3LfjO Hf SfOd GdMfajs; (3eMehO Hf YHjOGddg Hf EHQGgje GdeMHhHjj GdMfaj , HQgGf GdTQjYI,J (B673 (3g` s
(3ChdgG (B:s
(3MeO ef LYd GdYde CLd GdehGgH s
(3BNQgG (B:s
(3gPG BNQ GdcdGe hGdMeO ddg Ydi GdJeGe hYdi QShdg CaVd GdUdGI hGdSdGe s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdMfajs